2021
DOI: 10.1002/jcla.23819
|View full text |Cite
|
Sign up to set email alerts
|

Higher circular RNA_0015278 correlates with absence of extrathyroidal invasion, lower pathological tumor stages, and prolonged disease‐free survival in papillary thyroid carcinoma patients

Abstract: Background Circular RNA_0015278 (circ_0015278) inhibits the progression of several cancers and is greatly reduced in papillary thyroid carcinoma (PTC) tissues compared with benign thyroid lesions by microarray profiling. This study aimed to further investigate the correlation of circ_0015278 with tumor characteristics and prognosis in PTC patients. Methods Totally, 206 PTC patients who underwent tumor resection were retrospectively enrolled; subsequently, circ_0015278 expression in their tumor and adjacent tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Some circRNAs were vital for PTC progression. For example, Ding et al reported that high expression of hsa_circ_0015278 was associated with extrathyroidal invasion, pathological node stage, and reduced relapse rate 29 . Hsa_circ_102002 facilitated PTC cell migration and epithelial–mesenchymal transition 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Some circRNAs were vital for PTC progression. For example, Ding et al reported that high expression of hsa_circ_0015278 was associated with extrathyroidal invasion, pathological node stage, and reduced relapse rate 29 . Hsa_circ_102002 facilitated PTC cell migration and epithelial–mesenchymal transition 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Compared with normal controls, circRNAs present significantly differential expression profiles in TC tissues and blood from patients with TC; thus, they are regarded as promising and ideal candidates for the diagnosis of TC owing to their abnormal expression and high specificity (Table 2; Figure 4) (Jin et al, 2018;Lan et al 2018a;Ren et al 2018;Wang et al 2018b;Wei et al 2018;Cai et al 2019;Yao et al 2019;Wang et al 2019a;Fan et al 2020;Han et al 2020a;Hu et al 2020b;Liu et al 2020b;Sun et al 2020b;Wang et al 2020b;Wu et al 2020a;Xue et al 2020;Ye et al, 2020;Yu et al, 2020;Zhang et al 2020b;Chu et al, 2021;Ding et al 2021a;Ding et al 2021b;Du et al 2021;Guo et al 2021;Li et al 2021a;Li et al 2021b;Li et al 2021d;Lin et al 2021;Liu et al 2021b;Luo et al, 2021;Ma and Kan, 2021;Qi et al, 2021b;Xiong et al, 2021b;Zeng et al, 2021;Zhang et al 2021c;Zhang et al 2021d;Zheng et al 2021a;Zhu et al, 2021;…”
Section: Circrnas As Promising Diagnostic and Prognostic Biomarkers F...mentioning
confidence: 99%
“…Finally, defining a precise prognosis for TC patients is essential for physicians to formulate the best treatment decisions. To further analyse the prognostic value of circRNAs in TC, we collected information from studies reporting survival information and evaluated the associations between circRNA expression levels and overall survival (OS), disease-free survival (DFS), and progression-free survival (PFS) (Table 2) (Jin et al, 2018;Lan et al 2018a;Ren et al 2018;Wang et al 2018b;Wei et al 2018;Cai et al 2019;Yao et al 2019;Wang et al 2019a;Fan et al 2020;Han et al 2020a;Hu et al 2020b;Liu et al 2020b;Shi et al 2020;Sun et al 2020b;Wang et al 2020b;Wu et al 2020a;Xue et al 2020;Ye et al, 2020;Yu et al, 2020;Chu et al, 2021;Ding et al 2021a;Ding et al 2021b;Du et al 2021;Guo et al 2021;Li et al 2021a;Li et al 2021b;Li et al 2021d;Lin et al 2021;Liu et al 2021b;Luo et al, 2021;Ma and Kan, 2021;Qi et al, 2021b;Xiong et al, 2021b;Zeng et al, 2021;Zhang et al 2021c;Zhang et al 2021d;Zheng et al 2021a;…”
Section: Circrnas As Promising Diagnostic and Prognostic Biomarkers F...mentioning
confidence: 99%
“…hsa_circ_0062019 promotes prostate cancer cell proliferation, migration, and invasion through upregulating HMGA2 by decoying miR-195-5p [22]. Many other studies demonstrate the role of circRNAs in multiple cancer types such as thyroid, gastric, bladder, breast, and colon cancer [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%